Export marketing of cretan products - Chatzidimou E. (Strengthening endogenous development patterns in European agriculture, 1993)
This paper refers to the preliminary results of a research conducted in former European countries (Bulgaria, Albania, Hungary) intending to obtain a clear picture of their market structure. Further scope is to illustrate new markets for the Cretan agricultural products. Methodology employed is direct observation as well as secondary sources of information.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)